Traffic characteristic based privacy leakage assessment scheme for Android device - Zhu WANG; Kun HE; Xinyu WANG; Ben NIU; Fenghua LI (Tongxin xuebao)
Aiming at the privacy leakage,which was caused by collecting user information by third-party host in Android operating system App,a privacy leakage evaluation scheme HostRisk was proposed.HostRisk was based on TF-IDF model and hierarchical clustering method,which was applied in mobile device.The TF-IDF model calculated the business relevance between Apps and hosts via the behavior characteristics of the hosts in these Apps.For the business related hosts that fail to express the business relevance characteristics,those hosts were adjusted and optimized via the average connected hierarchical agglomerative clustering method.Finally,the harmful degree of privacy leakage was evaluated based on the ranking of all hosts in the App.The experimental results verify the effectiveness and efficiency of the scheme.